Development and evaluation of a mobile AAC: a virtual therapist and speech assistant for people with communication disabilities. (17th November 2018) - Wang, Erh-Hsuan; Zhou, Leming; Chen, Szu-Han Kay; Hill, Katya; Parmanto, Bambang
Abstract: Purpose: The currently existing Augmentative and Alternative Communication (AAC) technologies have limitations to produce the best communication rehabilitation outcomes and therefore a better solution is needed. Method: In this work, a mobile AAC app was developed based on results from research studies. Sophisticated AAC language programming, embedded training materials, and real-time communication performance reporting were integrated into the app. Two groups of study participants were recruited to participate a usability study and a preliminary feasibility study for the purpose of evaluating this mobile AAC app, respectively. Results: A tablet-based AAC app was developed to support communication rehabilitation. User studies of the app were conducted and included able-bodied individuals and people with verbal communication disabilities. All study participants agreed that the app establishes a usable alternative treatment protocol for communication rehabilitation. Conclusions: The app's integrated features have great potential to maximize users' communication effectiveness, enhance language skills, and ultimately improve users' quality of life. Implications for rehabilitation: We have developed and evaluated an integrated mobile AAC language-based app. This tablet-based app integrated AAC with embedded trainings and real-time performance report.